Characterization of physical and rehabilitation medicine prescription over a year in ACeS de Matosinhos - Amorim, M. Francisca (2024)
Introduction: Musculoskeletal disorders are one of the most frequent reasons for medical appointments in primary care. The high incidence of these pathologies also translates into a high need for rehabilitation care. This is why, in 2021, the prescription of physical and rehabilitation medicine (PRM) stood out as the second highest expense in the total costs of complementary means of diagnostic and therapeutic, in the North of Portugal. Thus, it is important to describe the main reasons for prescription. Objective: To describe the prescriptions of PRM appointments related to osteoarticular and musculoskeletal pathology, in the Matosinhos group of Family Health Units (FHUs). Methods: Observational and retrospective study of all PRM prescriptions carried out from January to December 2021 in 14 FHUs, with sociodemographic characterization of users and analysis of the number of prescriptions and codes of the International Classification of Primary Health Care associated with them. Results: The mean number of prescriptions per FHU was 1710.07. It was found that 47.94% of the prescriptions corresponded to the first PRM appointment, while 52.06% corresponded to the subsequent appointments. Most prescriptions were made to female patients (65.54%), exempted from paying user fees (58.65%), and mean age of 57.15 years. The most frequently coded health problem was L86 – Painful Spine Syndrome, followed by L92 – Painful Shoulder Syndrome, both for first and subsequent appointments. The pathologies that originated the highest number of subsequent prescriptions per user were multiple sclerosis and parkinsonism. It was also observed that 46.76% of the prescriptions were accompanied by an ICPC-2 code corresponding to a valid diagnosis for physiotherapy prescription. Conclusion: This is a relevant study that characterized PRM prescriptions and allowed us to understand the pathologies that led to the need for this care, which may constitute a starting point for improving the adequacy of health resources.